2017
DOI: 10.3892/mmr.2017.8203
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid�B recovers cognitive deficits and angiogenesis in a cerebral small vessel disease rat model via the STAT3/VEGF signaling pathway

Abstract: Salvianolic acid B is one of the key water‑soluble components of Salvia extract. It has been verified that salvianolic acid B possesses multiple pharmacological activities, it protects against myocardial infarction, however additionally improves injury of myocardial ischemia‑reperfusion. The present study, the possible effects of salvianolic acid B on cognitive deficits and angiogenesis in cerebral small vessel disease were investigated. Salvianolic acid B was identified to recover cognitive deficits and neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The signal transducer and activator of transcription pathway is involved in the IL-9-IL-9R interaction on astrocytes; unlike endothelial cells, astrocytes were activated by phosphorylated STAT3 but not phosphorylated STAT1 (11), which may contribute to the difference in cell types. Scholars have confirmed that salvianolic acid B can have a role in improving cognition and promoting angiogenesis by activating p-STAT3 to produce VEGF-A (23). Inhibition of the STAT3/VEGF-A pathway in vectors for non-small cell lung cancer would inhibit angiogenesis and promote tumor cell apoptosis (24).…”
Section: Discussionmentioning
confidence: 99%
“…The signal transducer and activator of transcription pathway is involved in the IL-9-IL-9R interaction on astrocytes; unlike endothelial cells, astrocytes were activated by phosphorylated STAT3 but not phosphorylated STAT1 (11), which may contribute to the difference in cell types. Scholars have confirmed that salvianolic acid B can have a role in improving cognition and promoting angiogenesis by activating p-STAT3 to produce VEGF-A (23). Inhibition of the STAT3/VEGF-A pathway in vectors for non-small cell lung cancer would inhibit angiogenesis and promote tumor cell apoptosis (24).…”
Section: Discussionmentioning
confidence: 99%
“…Sal B, an extract of S. miltiorrhiza , is used for the treatment of various vascular diseases involving the cardiovascular system ( Lin et al, 2016 ), cerebral small blood vessels ( Wang and Hu, 2018 ), and osteonecrosis of the femoral head in TCM ( Li and Wang, 2017 ). Ischemia and necrosis in the distal part of random skin flaps due to a reduced blood supply are commonly encountered in plastic and reconstructive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…et al, 2018 ; Yu and Liu, 2018 ), and HO1 is expressed during the oxidative stress response ( Fuyuno et al, 2018 ). Sal B promotes functional recovery from cerebral vessel disease by reducing oxidative stress ( Wang and Hu, 2018 ). Western blotting and IHC indicated that Sal B increased SOD1, eNOS, and HO1 expression in the dermis of ischemic flaps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations